Hybrid operating room with ceiling mounted imaging system assisted pre-operative and intra-operative lung nodule localization for thoracoscopic resections: a 5-year case series - Chia, Audrey Qi Xin (2024)
Background: Video-assisted thoracoscopic (VATS) lung resections are increasingly popular and localization techniques are necessary to aid resection. We describe our experience with hybrid operating room (OR) cone-beam computed tomography (CT) assisted pre-operative and intra-operative lesion localization of lung nodules for VATS wedge resections, including our novel workflow using the hybrid OR cone-beam CT to re-evaluate patients who have undergone pre-operative localization for those who are unsuitable for intra-operative localization. Methods: Retrospective analysis of all consecutive patients with small (≤ 20 mm), deep (≥ 10 mm distance from pleura) and/or predominantly ground-glass nodules selected for lesion localization in the Interventional Radiology suite followed by re-evaluation with cone-beam CT in the hybrid OR (pre-operative), or in the hybrid OR alone (intra-operative), prior to intentional VATS wedge performed by a single surgeon at our centre from January 2017 to December 2021. Results: 30 patients with 36 nodules underwent localization. All nodules were successfully resected with a VATS wedge resection, although 10% of localizations had hookwire or coil dislodgement. The median effective radiation dose in the pre-operative group was 10.4 mSV including a median additional radiation exposure of 0.9 mSV in the hybrid OR for reconfirmation of hookwire or coil position prior to surgery (p = 0.87). The median effective radiation dose in the intra-operative group was 3.2 mSV with a higher mean rank than the intra-operative group, suggesting a higher radiation dose (p = 0.01). Conclusions: We demonstrate that our multidisciplinary approach utilizing the hybrid OR is safe and effective. Intra-operative localization is associated with lower radiation doses. Routine use of cone-beam CT to confirm the position of the physical marker prior to surgery in the hybrid OR helps mitigate consequences of localization failure with only a modest increase in radiation exposure.